TEACHING ENGLISH PRONUNCIATION BY USING AUDIOLINGUAL METHOD: A STUDY AT SMPN 2 CAMPALAGIAN IN POLMAN REGENCY - Uswatun Hasanah; Dahniar , (Universitas Islam Negeri Alauddin Makassar, 2017)
: The objectives of this research were to find out the effectiveness using audiolingual method in Teaching English pronunciation at the Second Grade of SMPN 2 Campalagian. This research employed quasi-experimental method with two groups pre-test and post-test design. There were two variables in this research; they were independent variable and dependent variable, while independent variable was audiolingual method and dependent variable was students’ English pronunciation. The sample of the research consisted of 68 students which were taken by using Purposive Sample technique. The instrument at this research was English pronunciation test by using audiolingual. The result of the data indicated that there was no a significant difference between students’ pre-test in the experimental class and the control class and there was a significant difference between students’ post-test in experimental class and control class. This improvement is reinforced by the statistical analysis that t-test value was 10.29, it is greater than t-table value was1.997. Therefore, the researcher suggested that audiolingual method is effective in teaching English pronunciation.